DL-methionine supplementation in Japanese quails under different thermal conditions - Souza, Rannyelle Gomes; Maia, Maria Isabelly Leite; Anjos Lima, Luiz Arthur dos; Morais, Larissa Kellen da Cunha; Santos, Severino Guilherme Caetano Gonçalves dos; Veríssimo, Tarsys Noan Silva; Santos, José Danrley Cavalcante dos; Nascimento, Pavlos Vinícius do; Soares, Kilmer Oliveira; Costa, Fernando Guilherme Perazzo; Guerra, Ricardo Romão; Carvalho, Lucas Rannier Ribeiro Antonino; et al. (Frontiers in Animal Science, 2025)
Heat stress is one of the major constraints on quail production, compromising feed intake, egg quality, and overall welfare under tropical conditions. This study aimed to evaluate whether dietary methionine + cystine (Met+Cys) supplementation could mitigate the adverse effects of thermal stress on laying Coturnix japonica during peak egg production. A total of 504 female quails were distributed across 12 treatments in a 3 × 4 factorial design, combining three Met+Cys levels (100%, 110%, and 120% of NRC recommendations) and four ambient temperatures (20, 24, 28, and 32 °C). Over an 84-day trial, productive performance, egg quality, physiological markers (cloacal temperature, respiratory rate), and tissue morphology (duodenum, jejuno, hepatic, uterine) were evaluated. Heat stress markedly impaired reproductive performance and egg quality, particularly at 32 °C, with no significant interaction between temperature and supplementation level. Principal Component Analysis revealed structural degradation in intestinal, hepatic, and uterine tissues under elevated temperatures, partially alleviated by 120% Met+Cys at 24 °C. However, increased supplementation failed to reverse thermal-induced production losses under severe heat. These findings demonstrate that ambient temperature exerts a stronger influence than methionine and cysteine supplementation on overall quail performance. While nutritional interventions may help preserve tissue architecture under moderate heat stress (up to 28 °C), strategic thermal environment management remains the primary tool to safeguard welfare and productivity. This integrative approach underscores the value of multidimensional analysis in poultry science and supports refined thermal-nutritional management in quail production systems.